Constructing resilience at three scales: The 100 Resilient Cities programme, Durban's resilience journey and water resilience in the Palmiet Catchment. Issue 1 (March 2019) - Sutherland, Catherine; Roberts, Debra; Douwes, Jo
Resilience is a 're-emerging concept' which is being applied to deal with the shocks and stresses facing society and the environment as a result of both human induced and physical hazards. Resilience thinking is shaping policy and practice across the world through global programmes such as the UN Office for Disaster Risk Reduction (UNISDR)'s Making Cities Resilient Campaign; UN Habitat's City Resilience Profiling Programme; and Rockefeller Foundation's 100 Resilient Cities (100 RC). The global post-2015 sustainable development and climate change frameworks and related agreements all have resilience embedded in them. However, the concept of resilience remains contested, with resilience reflecting a continuum of approaches from those that are more deliberative, political, systemic, relational and transformational, to those that are more consultative, post-political, systems based, sectoral and instrumental. Questions of how resilience is being constructed, by whom and for whom therefore need to be explored. This paper focuses on the construction of resilience at three scales: The Rockefeller Foundation's 100 Resilient Cities (100RC) programme (global), Phase 1 of Durban's 100RC journey (city), and the Palmiet Catchment Rehabilitation Project (sub-catchment within a city). It presents the different approaches adopted by global, city-scale and local programmes to build resilience using different framings, approaches and methodologies.